Biophysical Characteristics on Nesting Habitat of Green Turtle Chelonia mydas in the Coastal Zone of Kasiak, Bindalang and Karabak Ketek Island of West Sumatra, Indonesia - Harfiandri Damanhuri; Dahelmi Dahelmi; Hafrijal Syandri; Dietriech G. Bengen (International Journal of Agricultural Sciences, 2019)
The research was conducted on three small islands of the marine conservation area of West Sumatra, namely Kasiak Island, Bindalang Island, and Karabak Ketek Island from January to December 2016. This research aimed to study the variation of the biophysical character of the nesting habitat of the green turtle (Chelonia mydas L, 1758) by survey method, measurement, observation, and analysis. All data were analyzed using Main Component Analysis (PCA), Kruskal Wallis Test Analysis. Based on PCA analysis, the contribution of the main character is 43.28%. These results are supported by biophysical conditions of spawning habitats for green turtles on Karabak Ketek Island as an ideal island of spawning sites favored by green turtles compared to the location of Bindalang Island and Kasiak Island habitats. Kruskal Wallis analysis of Karabak Island rank; 11.90, with a chi-square value; 10.47, sig value 0.005 (5% -10%). This value shows the difference between the spawning habitat's biophysical character on the character of the coastal slope parameter (KP) is 9.60°. It is also the ideal slope value for the sandy beach habitat (PSe) and fine sandy beaches (PHA) as the central spawning location for green turtles in West Sumatra